UTILIZATION OF LATRINE AND SEPTIC TANK CONTSTRUCTION BY THE DEPARTEMENT OF PUBLIC WORKS AND SPATIAL PLANNING SERVICE IN THE NUMBER OF OPEN DEFECATION IN THE VILLAGE OF DRIEN MANGKO, DISTRICTS WEST ACEH - Umi Kasum; Jun Musnadi Is (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Sanitation predicaments are all the more a characteristic disputed point encountered in indefinite territories and places, individual of which is in Drien Mangko Village, Woyla District, westbound Aceh rule in 2021, videlicet ODF administer defecation, thither are 62. in good health latrine sanitation has totality aggrandizement to everlasting in good health latrines JSP 29. 9%, semi-permanent in good health latrines JSSP 3 and all the more doing distribution (ride) 3. constituents causing ODF are little commensurate of economical capacity, general public are unqualified to satisfy becoming sanitation development. To bowled over this disputed point the westbound Aceh universal drudgeries and Spatial provisioning accommodation enforced a sanitation exploitation announcement in the community of Drien Mangko. The evaluation disposition put into practice a descriptive qualitative classification by conducting press conference approximately the discription of knowledge, dispositions and performances as advantageously as examinations on the superiority of latrines and abscessed tanks. The totality inhabitant is the beneficiaries in the configuration of Toilet washable and abscessed coolhead consisting of 9 families. The objective is to ascertain approximately the discription of the application of toilets and abscessed tanks that chalk up been reinforced by the universal drudgeries and Spatial provisioning occupation of westbound Aceh in 2021. The consequences established that 55. 6% chalk up first-class knowledge, 22. 2% chalk up adequate consciousness and deprivation of knowledge. 100% of respondents who chalk up a first-class attitude. 100% of respondents who chalk up first-class actions. The consequences of the examination that the interpretation of toilets and abscessed tanks is in conformation with wellness criteria with reference to in good health kith and kin latrines that buoy accommodate wellness requirements. The determination from the consequences is that respondents buoy application latrines and abscessed tanks advantageously so that the universal drudgeries and spatial provisioning division succeeded in reduction the ODF character in Drien Mangko community in 2022 nailed down the latrine and abscessed coolhead interpretation program.